An Application-Driven Framework for Intelligent Transportation Systems Using 5G Network Slicing - do Vale Saraiva, Tiago; Campos, Carlos Alberto Vieira; Fontes, Ramon dos Reis; Rothenberg, Christian Esteve; Sorour, Sameh; Valaee, Shahrokh (IEEE transactions on intelligent transportation systems, 2021)
Vehicular networks are critical pieces in support of advanced intelligent transportation systems (ITS). These networks are formed by vehicles that can be connected to one another as well as to the infrastructure, and are subject to constant topology changes, disconnections, and data congestion. Each ITS application could have a different set of communication requirements, such as delay, bandwidth, and packet delivery ratio. Meeting these heterogeneous requirements in the complex dynamic environment of vehicular networks is a challenge. This paper develops a new framework for application-driven vehicular networks using 5G network slicing. We present the architecture of the proposed solution and design algorithms for heterogeneous traffic in a dynamic vehicular environment. Our simulations on realistic vehicular scenarios show significant improvements in network performance compared to the state-of-the-art approaches.